PENGARUH DISIPLIN BELAJAR TERHADAP PRESTASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP AL-AZHAR MANDIRI PALU - Fatima, Siti; Rustina; Patanggu, Irawan Hadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was carried out to examine the effect of students’ learning discipline on their academic achievement in Islamic Religious Education at SMP Al-Azhar Mandiri Palu. This study uses a quantitative survey approach with a comparative causal design. The population included 187 eighth-grade students, while 65 participants were chosen as the sample using probability sampling through the Slovin formula with a 10% error tolerance. Data were obtained through observation and questionnaires. The analysis techniques consisted of descriptive statistics and inferential statistics, including regression analysis followed by a t-test. The data processing was supported by SPSS version 26 for Windows. The results indicated that learning discipline (X) has a significantinfluence on learning achievement (Y). This is supported by statistical evidence showing that the t-value is higher than the t-table value (2,234 > 1,998), with a significance value of 0.029 < 0.05. Moreover, the R-square value of 0.073 shows that learning discipline contributes 7,3% to students’ achievement.